2013
DOI: 10.2495/dne-v8-n4-265-286
|View full text |Cite
|
Sign up to set email alerts
|

The sustainable urban district of vauban in freiburg, germany

Abstract: The university town of Freiburg, Germany has a well-deserved reputation as the European capital of environmentalism and sustainable architecture and urban design. The city is perhaps best known for the development of two model sustainable urban districts, Rieselfeld and Vauban, both of which integrate multi-modal transportation linkages, ecological storm water management, low-energy passive solar houses, combined heating and power (CHP) systems, mixed uses (both public and private), local schools and a variety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 1 publication
2
38
0
Order By: Relevance
“…Typical district master planning for transportation aims to facilitate the flow of people within and across the district boundaries with adequate pedestrian malls and sidewalks, bike lanes, and group and public transportation infrastructure, in addition to personal vehicle accessibility (Coates, ; Kenworthy, ). Car‐, ride‐share, and automated bus infrastructure can incentivize the reduction of personal vehicles (Chance, ); integrated smart phone applications can facilitate group mobility.…”
Section: Sustainable District Planning Practicesmentioning
confidence: 99%
“…Typical district master planning for transportation aims to facilitate the flow of people within and across the district boundaries with adequate pedestrian malls and sidewalks, bike lanes, and group and public transportation infrastructure, in addition to personal vehicle accessibility (Coates, ; Kenworthy, ). Car‐, ride‐share, and automated bus infrastructure can incentivize the reduction of personal vehicles (Chance, ); integrated smart phone applications can facilitate group mobility.…”
Section: Sustainable District Planning Practicesmentioning
confidence: 99%
“…Moreover, car-sharing clubs are a distinctive feature of many car-free zones in Europe. These shared cars are not privately owned; and a limited fleet is permitted and sometimes promoted within or at the periphery of the car-free development to facilitate mobility (Coates, 2013). When further relaxation of allowing all private cars that meet certain air quality standards is applied, the area is called a 'low-emission zone' instead.…”
Section: Introductionmentioning
confidence: 99%
“…Travel behaviour data showed that residents of Rieselfeld had higher rates of transit use in an otherwise typical modal split, while Vauban's residents had extremely low car share and high bicycle share'. Still, Vauban only has a total population of about 5100 (Coates, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The Vauban neighbourhood, created in the 1990s, is called the "green neighbourhood" by the Freiburg city council [78]. Its origins go back to the Self-governed Independent Shelter Initiative (SUSI) [79]. The SUSI community, formed by young people seeking a new lifestyle system, set up an 'intentional community' [80,81].…”
Section: Solar Settlementmentioning
confidence: 99%